MENIAR EXTRACT NANO CONCENTRATE AND MILK PROCESSING TRAINING TO BOOST KELOMPOK PERAH JAYA JOMBANG'S INCOME - Hidanah, Sri; Sabdoningrum, Emy Koestanti; Al-Arif, Anam; Hasib, Fatin; Soeharsono, Soeharsono; Rahmawati, Kadek; Yudaniayanti, Ira (Universitas Airlangga, 2024)
Segunung is one of the six Dusun in Carangwulung, Wonosalam, Jombang, East Java where Sapi Perah Jaya and Wanita Tani Perah Jaya groups manage to breed 210 dairy cows. The milk produced is deposited to KUD Anjasmoro before being transferred to the milk processing industry and some is processed by Wanita Tani Perah Jaya into pasteurized milk. The problems faced by dairy farmers, especially after the Foot and Mouth Disease (FMD) outbreak, are the decreasing milk and feed production, and livestock health. The problem faced by Wanita Tani Perah Jaya is a lack of knowledge about dairy product verification and marketing. To solve this problem the researchers administer nano meniran extract containing bioactive compounds such as flavonoids and Saponin flavonoids, as an immunomodulator, stimulate and improve the immune system and the impaired immune function, while Saponins increase the diameter of the villi and the permeability of intestinal cell walls, thereby affecting the absorption of nutrients carried by feed. If the immunity increases and the absorption of feed nutrients is good, it will increase milk production in dairy cows. Through this community service activity, there will be increased empowerment of partners of the Sapi Perah Jaya Group with training in making concentrate with meniran nano extract as well as milk processing at the Wanita Tani Perah Jaya. The solution is to diversify milk in the form of yogurt. This activity was carried out using three methods: 1) Counseling on making beef concentrate with the addition of nano meniran extract, making yogurt and marketing dairy products, 2) Training on making the concentrate and making yogurt 3) Monitoring and evaluation that was carried out every month for 3 months after the counseling and training were carried out. The results obtained from this community service are the increased empowerment of partners and the increased skills of farmers in making concentrates and dairy products in the form of yogurt and marketing them. The successful application of technology through community service can increase the income and welfare of these two groups.